KEWIRAUSAHAAN DIGITAL DI KALANGAN MAHASISWA: STUDI LITERATUR - Alifia, Diva Ananda; Al Hafidh, Muharik Nahdloh; Arrasyid, Rakhmatan Lil Alamin; Gunawan, Muhammad Difa; Sobirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rise of the digital economy has created unprecedented opportunities, particularly for the younger generation. This study aims to provide a comprehensive analysis of the dynamics of digital entrepreneurship among university students through a systematic literature review. The research synthesizes findings from various academic sources to map the driving factors, significant barriers, and the critical role of the higher education ecosystem. The analysis reveals that students are motivated by a combination of intrinsic factors, such as the desire for autonomy and financial independence, and extrinsic factors, including technological accessibility and low entry barriers. However, their journey is fraught with challenges, most notably a competency gap between technical digital skills and strategic business acumen, limited access to capital, and difficulties in balancing academic responsibilities with business demands. This study underscores that universities play a pivotal role not merely as educational institutions but as central hubs in the entrepreneurial ecosystem. The development of integrated support systems including practice-based curricula, business incubators, mentorship programs, and industry partnerships is identified as a critical success factor. This paper concludes by offering strategic recommendations for universities, policymakers, and students to collaboratively foster a more vibrant and resilient generation of digital entrepreneurs. Keywords: Digital Entrepreneurship, Student Entrepreneurs, Entrepreneurial Ecosystem, Digital Literacy, Higher Education;